2019
DOI: 10.1097/jxx.0000000000000124
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an obstructive sleep apnea screening tool with hypertensive patients in the primary care clinic

Abstract: Background and Purpose: Patients with severe obstructive sleep apnea (OSA) have an almost 4-fold higher odds of resistant hypertension than those with less severe OSA. Obstructive sleep apnea screening practices in primary care are deficient. Additional study is needed regarding the value of OSA screening in hypertensive adults who present to the primary care clinic. Methods: This was a convenience sample of adults with hypertension from a rural primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The literature review suggests a high prevalence of underdiagnosed and undertreated OSA in 75–80% of the population with limitations in the current evidence supporting annual screenings (Aurora et al, 2015). This quality-improvement project aimed to support routine OSA screenings for asymptomatic high-risk patients, providing early evaluations, referrals, and treatment measures in the primary stages of OSA (Bakhai et al, 2017; Ononye et al, 2019; Showalter & O'Keefe, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The literature review suggests a high prevalence of underdiagnosed and undertreated OSA in 75–80% of the population with limitations in the current evidence supporting annual screenings (Aurora et al, 2015). This quality-improvement project aimed to support routine OSA screenings for asymptomatic high-risk patients, providing early evaluations, referrals, and treatment measures in the primary stages of OSA (Bakhai et al, 2017; Ononye et al, 2019; Showalter & O'Keefe, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, findings of Showalter and O’Keefe (2019) showed that 40% of hypertensive and obese patients were at high-risk for OSA, with 7.5% diagnosed with OSA (Showalter & O’Keefe, 2019). Findings of all three studies supported the implementation of screening measures such as the STOP-Bang Questionnaire to identify low, intermediate, or high levels of risk for OSA in asymptomatic patients with risk factors of hypertension and obesity (Bakhai et al, 2017; Ononye et al, 2019; Showalter & O’Keefe, 2019). They also recommended routine screening protocols to increase screenings and facilitate referrals for diagnostic testing in primary care (Bakhai et al, 2017; Ononye et al, 2019; Showalter & O'Keefe, 2019).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…OSA is highly and increasingly prevalent in adults, largely tracking with the obesity epidemic in developed countries (Peppard & Hagen, 2018). OSA is associated with a two- to threefold higher risk of cardiovascular and metabolic disease, with multiple studies linking OSA to the development of stroke, cardiac arrhythmias, and abnormalities in glucose metabolism (Tobaldini et al, 2019), and patients with severe OSA had an almost fourfold higher risk of resistant hypertension (Showalter & O’Keefe, 2019). As OSA is linked to a wide range of adverse health outcomes and mortality, it is critical to develop acceptable, feasible, and sustainable methods for identifying and treating patients with OSA.…”
Section: Targeting Sleep To Improve Cardiovascular Health Outcomesmentioning
confidence: 99%